2017
DOI: 10.3389/fcimb.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Virulence in Francisella tularensis

Abstract: Francisella tularensis, the causative agent of tularemia, is a Gram-negative bacterium that infects a variety of cell types including macrophages, and propagates with great efficiency in the cytoplasm. Iron, essential for key enzymatic and redox reactions, is among the nutrients required to support this pathogenic lifestyle and the bacterium relies on specialized mechanisms to acquire iron within the host environment. Two distinct pathways for iron acquisition are encoded by the F. tularensis genome- a siderop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
0
17
0
1
Order By: Relevance
“…Noteworthy, rhizoferrin encoding gene sequences have only been described in bacterial genomes so far [32,63] and coding sequences pertaining to the rhizoferrin operon in F. tularensis were used here to search for homologs in Mucor spp. In F. tularensis, genes involved in rhizoferrin synthesis and transport are located in an operon regulated by the Fur gene [34]. Based on these results, new candidate genes involved in rhizoferrin synthesis, import and export are proposed in the present study ( Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Noteworthy, rhizoferrin encoding gene sequences have only been described in bacterial genomes so far [32,63] and coding sequences pertaining to the rhizoferrin operon in F. tularensis were used here to search for homologs in Mucor spp. In F. tularensis, genes involved in rhizoferrin synthesis and transport are located in an operon regulated by the Fur gene [34]. Based on these results, new candidate genes involved in rhizoferrin synthesis, import and export are proposed in the present study ( Fig.…”
Section: Discussionmentioning
confidence: 66%
“…At least one ortholog of the R. delemar rfs gene, necessary for the carboxylate siderophore rhizoferrin production [33] was found in each Mucor species. Other genes that might be involved in this rhizoferrin-mediated iron uptake mechanism were identified based on their homology to the bacterial genes of the Francisella tularensis rhizoferrin operon [34]. Homologs of the FslB and FslC F. tularensis genes were detected in each Mucor genome and numerous potential Mucor genes belonging the major facilitator family matched to FslD.…”
Section: Iron Uptakementioning
confidence: 99%
“…Colour grading of solid line represents a serial of change folds of MBCs against different antibiotics, and the behaviours of various phenotypes (increase ranked as 1, and decrease ranked as −1) including growth in carbon resource medium, biofilm formation, ECPase and haemolytic activities. [Color figure can be viewed at wileyonlinelibrary.com] receptor mediates iron acquisition in host-bacteria interactions, the current work indicates these proteins should play multiple functions in biological processes, such as antibiotic resistance and virulence, besides iron transport (Ramakrishnan, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Besides this effect, unlike other siderophore receptors, ΔAHA_0461 also presents increasing ECPase and haemolytic activity in this study. Although many studies have documented that the TonB‐dependent siderophore receptor mediates iron acquisition in host–bacteria interactions, the current work indicates these proteins should play multiple functions in biological processes, such as antibiotic resistance and virulence, besides iron transport (Ramakrishnan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one of the effectors, a cell membrane-localized iron transporter, IroT, was reported to be involved in ferrous iron acquisition and the mutant is defective in intracellular growth in A. castellanii and macrophage ( Portier et al, 2015 ). Iron-dependent virulence is widely distributed among bacterial pathogens ( Reinhart and Oglesby-Sherrouse, 2016 ; Butt and Thomas, 2017 ; Ramakrishnan, 2017 ). Although there are limited evidences showing that iron-regulated virulence factors contribute to grazing resistance, it has been reported that E. coli strains encoding genes for iron uptake survived better with D. discoideum than avirulent strains lacking these genes ( Adiba et al, 2010 ).…”
Section: Intracellular Pathogensmentioning
confidence: 99%